KOMPOSISI JENIS IKAN DI PERAIRAN SUNGAI BUMANG KECAMATAN MENDO BARAT KABUPATEN BANGKA - Muhammad Sohibud Daim; Andi Gustomi; Eva Utami (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
Bumang River is one of rivers which located in district of Mendo Barat, Bangka Regency. construction of dams and construction of reservoirs at the river that lead to decreasing of the quality of the environment, especially for the biodiversity of fish. The aim of this research was to investigate the diversity of fish, similarity index and domination index of fish in Bumang River, district of Mendo Barat, Bangka regency. The method used was survey-sampling method by placing two observation stations in way of purposive sampling. It was divided on certain stations, such as up and down stream station. The data collected was chemical and physicalwater parameters and fish sample by using gillnet. The result shows that 8 fish species in Bumang River in District of Mendo Barat, Bangka Regency.composed of 7 genus and 5 families were found. The diversity of fish population and species in Bumang River indicating on low and average range and was not dominate by certain species. Taken together, the populations of fish in Bumang River were uniform